Differences

This shows you the differences between two versions of the page.

Link to this comparison view

Both sides previous revision Previous revision
drastic_measures [2016/07/17 15:24]
nikolaj
drastic_measures [2016/07/17 15:28] (current)
nikolaj
Line 16: Line 16:
 $N_Sf:​=(Sf)^{-1}\cdot f$, $N_Sf:​=(Sf)^{-1}\cdot f$,
  
-which we'll also write as+has $SN_Sf=e$ and $[N_S]=[S^{-1}]$.
  
-$\bar{f}:​=(Sf)^{-1}\cdot f+As $Sis linear, ​
  
-has $S\bar{f}=e$.+$N_S(c\,​f)=N_S(f)$ 
 + 
 +We'll also write 
 + 
 +$\bar{f}:=(Sf)^{-1}\cdot f
  
 == Example 1 == == Example 1 ==
Link to graph
Log In
Improvements of the human condition